PENGEMBANGAN PEMBELAJARAN IPS TERPADU MELALUI MEDIA PIE CHART UNTUK MENINGKATKAN HASIL BELAJAR - Arga, Kharisma Idola (LPPM STKIP PGRI Bandar Lampung, 2017)
This research aimed to develop social study learning through Pie Chart and to know the effectiveness of learning through Pie Chart in social study learning. The research method used was research and development (R&D). The desain of learning development through Pie Chart used the step of Dick and Carey. The researcher used purpose sampling in taking tke sample of the research. The researcher took two classes VII3 as the control and VII6 as experiment class. The research result of this learning development concluded that, (1) This research was the development of social study learning through Pie Chart to increase the study result of the student in seven grade of SMP Wiyata Bhkati Natar Sout Lampung 2015/2016; (2) The study result of posttest in experiment class that used Pie Chart in social studies learning was higher than the control class that used conventional learning.